2015
DOI: 10.1111/jsbm.12176
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social and Human Capital in Developing Young Women as Entrepreneurial Business Leaders

Abstract: The authors explore the influence of social and human capital in defining the prospects of young women business owners as emerging entrepreneurial leaders. They propose a number of factors that mean many young women seeking to assume an entrepreneurial leadership role in society are insufficiently resourced in terms of their social and human capital. Such deficits have consequences for the effectiveness of their leadership potential and the development of their enterprises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 56 publications
(119 reference statements)
2
80
0
3
Order By: Relevance
“…Social capital is an important element for new venture creation (Debrulle et al 2014) and startup growths (Pirolo and Presutti 2010). Studies found social capital enhancing and incubating entrepreneurship, business growth in microentrepreneurs and small enterprises (Kickul et al 2007;Cruickshank and Rolland 2006;Honig and Karlsson 2010;McGowan et al 2015;Roomi 2013). Social capital played an important role in the entrepreneurial process for accessing tangible and intangible resources (Ferri et al 2009).…”
Section: Literaturementioning
confidence: 98%
“…Social capital is an important element for new venture creation (Debrulle et al 2014) and startup growths (Pirolo and Presutti 2010). Studies found social capital enhancing and incubating entrepreneurship, business growth in microentrepreneurs and small enterprises (Kickul et al 2007;Cruickshank and Rolland 2006;Honig and Karlsson 2010;McGowan et al 2015;Roomi 2013). Social capital played an important role in the entrepreneurial process for accessing tangible and intangible resources (Ferri et al 2009).…”
Section: Literaturementioning
confidence: 98%
“…The literature also ignores the variety of networking activities and needs that exist. For example, McGowan et al (2015) observe that young female entrepreneurs are frustrated with existing networks, as they do not accommodate their needs. Furthermore, the similarities between men and women's networking activities (e.g.…”
Section: Business Networking/social Capitalmentioning
confidence: 99%
“…These include claims that the gender gap in venture creation is associated with gender differences in social networks (Brush, Kelley, Litovsky, & Green, ; Klyver & Grant, ) and in the different ways men and women possess entrepreneurial social capital (Shaw, Marlow, Lam, & Carter, ). Others outline specific ways of networking that women find conducive to growing their businesses (Bogren, von Friedrichs, Rennemo, & Widding, ) and outline ways women should network to develop entrepreneurial capacity (McGowan, Cooper, Durkin, & O'Kane, ). Further, research in this stream suggests that women working in gender non‐traditional fields, such as technology, have reduced social capital (Sappleton, ), which may lead to their marginalization from ‘information, influence, and solidarity benefits’ and thus, suppress entrepreneurship (Light & Dana, , pp.…”
Section: Introductionmentioning
confidence: 99%